Awareness regarding diabetes mellitus among individuals attending a hospital, Bhaktapur - Kafle, Rita; Pradhan, Binita; Chandyo, Ram Krishna (Journal of Kathmandu Medical College, 2019)
Background: Diabetes mellitus is the most prevalent metabolic condition and one of the major health and socioeconomic problems worldwide. Awareness of risk factors and prevention of diabetes plays a major role for prevention of diabetes mellitus in general population.Objectives: To assess level of awareness regarding diabetes mellitus risk factors and preventive measures among individuals who attended General Practice outpatient department at Kathmandu Medical College Teaching Hospital, Duwakot, Bhaktapur.Methodology: This is a descriptive study conducted in Department of General Practice and Emergency of Kathmandu Medical College Teaching Hospital. The study included 370 patients attending General Practice outpatient department from November 2018 to April 2019. The data collected was entered in the Statistical Package for the Social Sciences software and analysed for results. Ethical clearance was taken from Institutional Review Committee of Kathmandu Medical College.Results: The study included 370 participants; the mean age was 40.83±12.21 years. More than half of the participants (56.5%) were females and 43.5% were males. The most commonly mentioned risk factor was lack of physical activity and obesity. Almost 80% participants correctly stated that physical activity could help prevent diabetes mellitus. There was no statistical significance between awareness and educational level of participants.Conclusion: This study showed that proper awareness programs need to be carried out in rural and urban communities to prevent diabetes and its complications. In this study, patient awareness about risk factors and preventive measures was not appreciable. Association of awareness with age, sex and education level was not statistically significant.